NOUN PHRASES IN THE INTERLANGUAGE OF CHINESE UNIVERSITY STUDENTS LEARNING ITALIAN AS A SECOND FOREIGN LANGUAGE: A CORPUS STUDY (Italiano LinguaDue, 2025)
The present study shows the results of a longitudinal research on a corpus of oral productions by Chinese learners of Italian as a Second Language in an academic context. The study presents the theoretical underpinnings on corpora research and the state of the art for the Italian language as well as the studies done on the development of the interlanguage and the acquisitional theories underlying the process of language acquisition concerning the Italian language. Specifically, it focuses on the patterns of acquisition of the noun phrase. Successively, the methodology of the research is explained and the data is presented and statistically analysed. Finally, pedagogical suggestions are drawn from the data gathered. Il sintagma nominale nell’interlingua di studenti universitari cinesi che apprendono l’italiano come lingua seconda: un corpus studyIl presente studio mostra i risultati di una ricerca longitudinale su un corpus di produzioni orali di apprendenti cinesi di italiano come seconda lingua in un contesto accademico. Lo studio presenta i fondamenti teorici sulla ricerca sui corpora e sullo stato dell'arte della lingua italiana nonché gli studi condotti sullo sviluppo dell'interlingua e le teorie acquisizionali alla base del processo di acquisizione linguistica riguardante la lingua italiana. Nello specifico, si concentra sui modelli di acquisizione della frase nominale. Successivamente viene spiegata la metodologia della ricerca e i dati vengono presentati e analizzati statisticamente. Dai dati raccolti, infine, si traggono suggerimenti pedagogici.